PENGARUH INTENSITAS SCREEN TIME GADGET TERHADAP HASIL BELAJAR FIQIH SISWA KELAS VII B MADRASAH TSANAWIYAH AL ISLAM JAMSAREN SURAKARTA - Siti Cholilah; Nur Hidayah (STKIP Pesisir Selatan, 2026)
This study aims to analyze the effect of gadget screen time intensity on the learning outcomes of Fiqh subjects among Grade VII B students at MTs Al Islam Jamsaren Surakarta in the 2025/2026 academic year. The rapid development of digital technology has increased gadget usage among adolescents, including Islamic junior high school students. Uncontrolled gadget use may affect students’ concentration, motivation, discipline, and academic achievement. This research employed a quantitative approach using a survey method. The participants consisted of 32 students of Grade VII B. Data collection techniques included questionnaires to measure gadget screen time intensity and documentation of students’ Fiqh learning outcomes. Data were analyzed using descriptive statistics and simple linear regression with the assistance of SPSS software. The results indicated that students’ gadget screen time intensity was categorized as moderate with an average score of 53.00 or 68.8%. Meanwhile, students’ Fiqh learning outcomes were also categorized as moderate with an average score of 84.18 or 78.1%. The simple linear regression analysis showed a significance value of 0.004 < 0.05, indicating a significant effect of gadget screen time intensity on students’ Fiqh learning outcomes. The coefficient of determination revealed that the influence contribution reached 24.1%, while the remaining percentage was affected by other external factors.